Performance Culture as an Enhancement Aspect of Counselor Professional Competency - Kiswanto, Andi (JOMSIGN: Journal of Multicultural Studies in Guidance and Counseling, 2018)
The aim of this study is to find out the performance culture of teachers guidance and counseling in schools that become aspects of professional competence booster. The scope of this study covers five dimensions of performance culture: Power distance, Uncertainty avoidance, individualism-collectivism, masculinity-femininity, and time orientation. The method used is descriptive analysis. The results of this study are to show low criteria in dimension Power distance, height in the dimension of uncertainty avoidance, is collectivism, femininity and has long-term oriented time.